Monitoring of the Orbital Position of a Geostationary Satellite by the Spatially Separated Reception of Signals of Digital Satellite Television - Kaliuzhniy, M.P.; Bushuev, F.I.; Sibiriakova, Ye.S.; Shulga, O.V.; Shakun, L.S.; Bezrukovs, V.; Kulishenko, V.F.; Moskalenko, S.S.; Malynovskyi, Ye.V.; Balagura, O.A. (Science and Innovation, 2024)
The results of the determination of the geostationary satellite «Eutelsat-13B» orbital position obtained during 2015-2016 years using European stations’ network for reception of DVB-S signals from the satellite are presented. The network consists of five stations located in Ukraine and Latvia. The stations are equipped with a radio engineering complex developed by the RI «MAO». The measured parameter is a time difference of arrival (TDOA) of the DVB-S signals to the stations of the network. The errors of TDOA determination and satellite coordinates, obtained using a numerical model of satellite motion, are equal ±2.6m and ±35m respectively. Software implementation of the numerical model is taken from the free space dynamics library OREKIT.